Strategies to Improve the Performance of Li Metal Anode for Rechargeable Batteries - Hu, Zhongliang; Li, Jingying; Zhang, Xiaojing; Zhu, Yirong (Frontiers in Chemistry, 2020)
Li metal batteries have been considered as the most promising batteries with high energy density for cutting-edge electronic devices such as electric vehicles, autonomous aircrafts and smart grids. However, Li metal anode faces the issues of safety and capacity deterioration, which are closely related to Li dendrite growth. In this paper, we review the main strategies to improve the performance of Li metal anode. Due to Li dendrite’s catastrophic influence, suppression of Li dendrite growth is prerequisite for each strategy. Apart from Li dendrite, interfacial resistance between electrolyte and electrode, ionic conductivity of electrolytes, mechanical strength and volume fluctuation of Li metal anode are also discussed in these strategies. We outline these strategies based on the classifications of construction of SEI, engineering of solid-state electrolyte and adopting matrix for Li metal anode. Each strategy was illustrated and discussed in detail by exemplification. For better understanding, some important theories related to Li metal anode had been also introduced. Finally, general conclusions and the outlooks for future research and development of Li metal anode are presented.